Does Housing Status Matter in Emergency Medical Services Administration of Naloxone? A Prehospital Cross-sectional Study - Tiffany M. Abramson; Corey M. Abramson; Elizabeth Burner; Marc Eckstein; Stephen Sanko; Suzanne Wenzel (Western Journal of Emergency Medicine, 2023)
Introduction: Persons experiencing homelessness (PEH) use emergency medical services (EMS) at disproportionately high rates relative to housed individuals due to several factors including disparate access to healthcare. Limited access to care is compounded by higher rates of substance use in PEH. Despite growing attention to the opioid epidemic and housing crisis, differences in EMS naloxone administration by housing status has not been systematically examined. Our objective in this study was to describe EMS administration of naloxone by housing status in the City of Los Angeles. Methods: This was a 12-month retrospective, cross-sectional analysis of electronic patient care reports (ePCRs) for all 9–1–1 EMS incidents attended by the Los Angeles Fire Department (LAFD), the sole EMS agency for the City of Los Angeles during the study period, January-December 2018. During this time, the City had a population of 3,949,776 with an estimated 31,825 (0.8%) PEH. We included in the study individuals to whom LAFD responders had administered naloxone. Housing status is a mandatory field on ePCRs. The primary study outcome was the incidence of EMS naloxone administration by housing status. We used descriptive statistics and logistic regression models to examine patterns by key covariates. Results: There were 345,190 EMS incidents during the study period. Naloxone was administered during 2,428 incidents. Of those incidents 608 (25%) involved PEH, and 1,820 (75%) involved housed individuals. Naloxone administration occurred at a rate of 19 per 1,000 PEH, roughly 44 times the rate of housed individuals. A logistic regression model showed that PEH remained 2.38 times more likely to receive naloxone than their housed counterparts, after adjusting for gender, age, and respiratory depression (odds ratio 2.38, 95% confidence interval 2.15–2.64). The most common impressions recorded by the EMS responders who administered naloxone were the same for both groups: overdose; altered level of consciousness; and cardiac arrest. Persons experiencing homelessness who received naloxone were more likely to be male (82% vs 67%) and younger (41.4 vs 46.2 years) than housed individuals. Conclusion: In the City of Los Angeles, PEH are more likely to receive EMS-administered naloxone than their housed peers even after adjusting for other factors. Future research is needed to understand outcomes and improve care pathways for patients confronting homelessness and opioid use.